The Inclusion of Standards of Integrations between Science Technology Society and Environment (STES) in the Sciences Textbooks in Jordan: Analytical Study - AlTamimi, Hedaya Radwan; Arouri, Yousef Mhmoud (Dirasat: Educational Sciences, 2024)
Objectives: The study aims to identify the extent to which the criteria of the Science, Technology, Society, and Environment (STSE) approach are incorporated into the biology, physics, earth science, and chemistry textbooks for the 10th grade in Jordan. Methods: The descriptive-analytical method was employed to achieve the study’s objectives. A tool for analysis was developed, consisting of eight domains, which were validated for reliability and accuracy. Results: The results showed that the highest percentage of STSE criteria incorporation was in the 10th-grade biology textbook, with 41%, followed by the earth science textbook at 32%, the chemistry textbook at 16%, and finally the physics textbook at 11%. These percentages were compared to the inclusion of STSE criteria in the 10th-grade biology textbook. The findings also revealed statistically significant differences in the incorporation of STSE criteria across the chemistry, physics, biology, and earth science textbooks, in favor of the biology textbook, followed by the earth science textbook, then the chemistry textbook, and finally the physics textbook. Conclusion: The study concluded that there is a need to develop the physics and chemistry curricula for the 10th grade, with a focus on incorporating STSE criteria and addressing issues related to the student’s environment and society.